2022
DOI: 10.3389/fimmu.2022.841126
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against Proteins Previously Associated With Autoimmunity in Adult and Pediatric Patients With COVID-19 and Children With MIS-C

Abstract: The antibody profile against autoantigens previously associated with autoimmune diseases and other human proteins in patients with COVID-19 or multisystem inflammatory syndrome in children (MIS-C) remains poorly defined. Here we show that 30% of adults with COVID-19 had autoantibodies against the lung antigen KCNRG, and 34% had antibodies to the SLE-associated Smith-D3 protein. Children with COVID-19 rarely had autoantibodies; one of 59 children had GAD65 autoantibodies associated with acute onset of insulin-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The successful treatment of MIS-C with intravenous immunoglobulin (IVIG) and steroids further implicates systemic immune dysregulation in disease pathogenesis ( Belhadjer et al, 2020 ; Crosby et al, 2021 ). While circulating autoantibodies reactive to endothelial cell components may account for the cardiovascular dysfunction in acute MIS-C ( Burbelo et al, 2022 ; Porritt et al, 2021a ; Ramaswamy et al, 2021 ), the underlying mechanisms for mucosal tissue damage remain unclear. It is also not known whether the systemic inflammation observed in MIS-C is induced by SARS-CoV-2 infection or secondary effects of immune activation and/or tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…The successful treatment of MIS-C with intravenous immunoglobulin (IVIG) and steroids further implicates systemic immune dysregulation in disease pathogenesis ( Belhadjer et al, 2020 ; Crosby et al, 2021 ). While circulating autoantibodies reactive to endothelial cell components may account for the cardiovascular dysfunction in acute MIS-C ( Burbelo et al, 2022 ; Porritt et al, 2021a ; Ramaswamy et al, 2021 ), the underlying mechanisms for mucosal tissue damage remain unclear. It is also not known whether the systemic inflammation observed in MIS-C is induced by SARS-CoV-2 infection or secondary effects of immune activation and/or tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…showed that autoantibodies are present in approximately 15% of healthy controls and 50% of COVID-19 patients against commonly recognized antigens in an array of autoimmune disorders, including SSA/Ro52 [38]. However, Burbelo, et al, 2022 demonstrated that a considerable fraction of the autoantibody positivity in severe COVID-19 subjects may be related to receipt of intravenous immunoglobulins (IVIG) [39]. Thus, these results suggest the need for longitudinally sampled and controlled serosurveillence need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some studies reported that children with MIS-C have a concomitant expansion of antibodies against other common respiratory viruses, including other coronaviruses, influenza, respiratory syncytial, and Epstein-Barr viruses [16]. Notably, children with MIS-C also show high levels of circulating autoantibodies, which were also found in samples taken prior to intravenous immunoglobulins (IVIG) administration [50,52,53].…”
Section: Multisystem Inflammatory Syndrome In Children and Autoimmuni...mentioning
confidence: 99%